Relevansi Pendekatan Mazhab dalam Hukum Islam Kontemporer: Tinjauan Literatur - Wildan Fikri Ansyah; Hilma Aisya; Novilda Fitriningrum; Ummi Habibah; Siyono (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
This article examines the relevance of the madhhab approach in shaping contemporary Islamic law through a comprehensive literature review. Rapid developments in modern social, economic, and technological contexts require more adaptive legal methodologies, while the classical madhhabs remain essential for providing structured usul al-fiqh principles and methodological foundations. This study aims to evaluate the extent to which madhhabs still function as a methodological basis, how they interact with modern forms of ijtihad, and how contemporary scholars integrate classical heritage with present-day demands. Using a descriptive–thematic literature review method, data were collected from accredited journals, scholarly books, and contemporary fatwas. The findings indicate that the madhhab tradition remains relevant when interpreted dynamically and aligned with the objectives of Islamic law (maqāṣid al-sharī‘ah). Madhhabs continue to serve as analytical frameworks that can be combined with modern ijtihad, collective reasoning, and interdisciplinary approaches to address emerging issues such as digital finance, bioethics, and technological advancements. However, the study also identifies inherent historical limitations within the madhhab system, which necessitate methodological renewal to maintain practical relevance in contemporary legal challenges. Overall, the article highlights the importance of harmonizing classical tradition with contextual approaches as a foundation for developing modern Islamic legal epistemology.